2018
DOI: 10.1007/s00384-018-3043-5
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative radiotherapy is an independent risk factor for major LARS: a cross-sectional observational study

Abstract: Perioperative radiotherapy is an independent risk factor for major LARS. Fragmentation is considered the most disabling complaint in the majority of patients with major LARS. There is no significant adaptation of the LARS score over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…Therefore, we resigned from presenting incomplete data in order to avoid bias due to different time of follow-up. We also did not analyse other types of surgery factors that may contribute to LARS development, for example, the type of radiotherapy [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we resigned from presenting incomplete data in order to avoid bias due to different time of follow-up. We also did not analyse other types of surgery factors that may contribute to LARS development, for example, the type of radiotherapy [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Perioperative radiotherapy is a risk factor of faecal incontinence 6 months after the surgery. Other authors also identified neoadjuvant radiotherapy as a factor leading to LARS [ 26 , 42 , 43 ]. Postoperative radiotherapy also causes deterioration of anal sphincter function [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic technique resulted in a lower LARS score according to Nuytens et al [ 42 ]. In contrast, a meta-analysis performed by Lim et al showed no difference between minimally invasive and open approaches regarding sexual and bladder functions [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…After LAR and colorectal anastomosis, patients often have increased stool frequency, urgency, stool fractionation and faecal incontinence. These symptoms are even more severe after neoadjuvant therapy, which is an independent risk factor for worse bowel function after LAR.…”
Section: Introductionmentioning
confidence: 99%